Brief: a global water data infrastructure for a resilient hydrological cycle - Adolfsson, E. (International Water Management Institute, 2025)
Climate change and unsustainable land and water use are disrupting the global hydrological cycle, threatening economies, livelihoods, and ecosystems. Safeguarding a resilient water cycle and stable green water (soil and plant moisture, evapotranspiration) and blue water (rivers, lakes, groundwater) requires systemic, collective, and economy-wide action. To transform the way we value water, the Global Commission proposes five missions to drive innovation in policies, institutions, and technologies.